Charter schools in action : renewing public education - Finn, Chester E., Jr., 1944-; Manno, Bruno V.; Vanourek, Gregg (Princeton University Press, 2000)
Can charter schools save public education? This radical question has unleashed a flood of opinions from Americans struggling with the contentious challenges of education reform. There has been plenty of heat over charter schools and their implications, but, until now, not much light. This important new book supplies plenty of illumination. Charter schools--independently operated public schools of choice--have existed in the United States only since 1992, yet there are already over 1,500 of them. How are they doing? Here prominent education analysts Chester Finn, Bruno Manno, and Gregg Vanourek.